“Num abraço, multidões!”: o direito à fraternidade, a declaração dos direitos do homem e do cidadão e a nona sinfonia de Beethoven - Morais, Nicole Leite (2020)
In the context of the historical evolution of Human Rights, the 17 articles of the Declaration of the Rights of Man and the Citizen were influenced by the motto of the French Revolution liberté, égalité, fraternité. However, although the rights to freedom and equality are expressed in the text of the declaration, in its article 1, it is clear that the same is not true for the right to fraternity. Based on this problem, the following question arises in the present research: Can a song fill a legal gap? Or, more specifically, can Beethoven’s Ninth Symphony guide the interpretation to the point of filling the gap in the right to fraternity in the Declaration of the Rights of Man and of the Citizen? It can be seen that Beethoven, when using the poem An die Freude, by Schiller, in the composition of the fourth movement of the Ninth Symphony, conveyed the message contained in Schiller’s verses, that all men are brothers, in direct reference to the object of the present research, namely, the right to fraternity. In this sense, considering the exaltation of the fraternity through Beethoven’s Ninth Symphony, we hypothesize the possibility of this Symphony guiding the interpretation of the Declaration, thus bridging the gap in the right to fraternity. The central objective of this research, therefore, is to analyze the possibility of bridging the gap in the right to fraternity in the Declaration of the Rights of Man and of the Citizen through Beethoven’s Ninth Symphony. In order to achieve the proposed objective, in this research, we opted for the use of a qualitative approach, of the exploratory and deductive type, making use of bibliographic and documentary techniques, using information from different national and international sources, and keeping in mind the following categories of analysis: transjuridity; human rights; art and education; fraternity; Beethoven’s Ninth Symphony. The research reveals that Beethoven’s Ninth Symphony, particularly its fourth movement, the Coral, can function as an instrument to address the right to fraternity, as a symbol of unity between peoples.